X(15x+11)+2=0

Simple and best practice solution for X(15x+11)+2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(15x+11)+2=0 equation:


Simplifying
X(15x + 11) + 2 = 0

Reorder the terms:
X(11 + 15x) + 2 = 0
(11 * X + 15x * X) + 2 = 0
(11X + 15xX) + 2 = 0

Reorder the terms:
2 + 11X + 15xX = 0

Solving
2 + 11X + 15xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + 11X + -2 + 15xX = 0 + -2

Reorder the terms:
2 + -2 + 11X + 15xX = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 11X + 15xX = 0 + -2
11X + 15xX = 0 + -2

Combine like terms: 0 + -2 = -2
11X + 15xX = -2

Reorder the terms:
2 + 11X + 15xX = -2 + 2

Combine like terms: -2 + 2 = 0
2 + 11X + 15xX = 0

The solution to this equation could not be determined.

See similar equations:

| 4y-10=2y+5 | | 4x-9=-6+5x | | -4.9t^2+24.5t+2=0 | | 7x+3x-4x=3-3(x+4) | | 139=-5-2(4+8P) | | (5x^3y^2-3xy^5+12x^2)-(-9x^2-8x^3y^2+2xy^5)=0 | | 4x-9=-6+-5x | | 3x(-3)+b= | | 7-3a=11+a | | X(15x+11x)+2=0 | | 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 |

Equations solver categories